Risk and Protective Factors for COVID-19 Infection among Pregnant Women with Sickle Cell Trait - Kim Abbegail Tan Aldecoa; Camelia Arsene; Geetha Krishnamoorthy; Tiffany Chng; Garrett Cherry; Nabila Chowdhury; Ryan Clark; Dana Deeb; Lisa Deptula; Grey Dietz; Ewomamobuho Eto; Victoria Golston; et al. (Advances in Hematology)
Pregnant women and individuals with sickle cell trait (SCT) and underlying comorbidities are both independently more vulnerable to severe illness from coronavirus disease 2019 (COVID-19) compared to nonpregnant women and those without SCT. However, our understanding of the specific factors influencing susceptibility to COVID-19 infection among pregnant women with SCT is currently constrained by limited available data. This study aims to determine the risk and protective factors that influence the likelihood of COVID-19 infection in this population. A retrospective analysis was done among 151 women with SCT in the reproductive age group. Multivariable analysis was performed to determine the various factors affecting COVID-19 infection among pregnant women with SCT. The study found that COVID-19-vaccinated pregnant women with SCT had a 90% lower risk of contracting COVID-19 and were 9 times more likely to have a COVID-19 infection if they had a history of pulmonary conditions such as asthma or chronic obstructive pulmonary disease. The present study further emphasizes the importance of the COVID-19 vaccine in preventing infection and safeguarding the health of pregnant women with SCT, particularly those with underlying comorbidities.